Application of real-time PCR assays for the diagnosis of histoplasmosis using three molecular targets in human FFPE tissues and whole-blood (2018)
Objective: Histoplasmosis is a fungal infection that causes significant morbidity and mortality in persons living with HIV/AIDS, especially in countries with limited resources. Currently used diagnostic tests rely on culture and serology, lack sensitivity and often require weeks to obtain results causing significant diagnosis delays; molecular assays are not commercially available. Methods: we aimed to apply quantitative real-time PCR (qPCR) targeting three protein-coding genes of Histoplasma capsulatum (100-kDa, H and M antigens) for detection of H. capsulatum infection in formalin-fixed paraffin-embedded (FFPE) and whole blood (WB) samples from patients with proven histoplasmosis. Results: For FFPE samples, the sensitivity of 100-kDa, H and M qPCR assays were 93.9%, 91% and 57%, respectively; however, the same qPCR assays showed only 23%, 19% and 11.5% of sensitivity for 100-kDa, H y M qPCR assays when used with the WB samples. The specificity of qPCR was determined by testing samples from patients with other clinical infections and healthy controls and was 93%-100% depending upon the assay and the specimen type. Conclusion: we applied three qPCR assays for detecting H. capsulatum DNA in human samples, and demonstrated that the molecular protocols based on amplification of 100-kDa and H antigen can be successfully used for diagnosing this mycosis when using FFPE samples; however, we do not recommend WB for routine diagnosis of histoplasmosis by qPCR in patients with progressive disseminated histoplasmosis.